Performance excellence measurement framework : a study of hotel industry in Bangladesh - Rahman, Md. Mahbubar (Kuliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
The past decades have seen the development of numerous quality awards and excellence frameworks such as ISO, Deming Prize, Malcolm Baldrige National Quality Award (MBNQA), and European Foundation Quality Management (EFQM). More than 80 countries have successfully applied these frameworks in various sectors to achieve excellence in their businesses. Most of the Asian countries follow the MBNQA with little modification. However, the business sector in Bangladesh displayed limited efforts in following a framework for measuring performance excellence in a structured and systematic manner. This study filled the void by developing a framework that enables ranking of the criteria and sub-criteria for achieving business excellence in the hotel industry of Bangladesh. The specific objectives of the study are to: (1) identify the most frequently used business excellence models that can be used as theories for developing a performance excellence measurement framework for the hotel industry of Bangladesh, (2) identify the necessary criteria and sub-criteria to develop a new framework for the hotel industry, (3) prioritise the criteria and sub-criteria in the course of developing the new performance excellence measurement framework, and (4) operationalise the new framework and evaluate the performance level of some selected hotels in Bangladesh. This study adapted the sequential mix method process by combining qualitative and quantitative approaches. Semi structured interviews with 24 participants were initially conducted to identify the criteria and sub-criteria. Subsequently, a questionnaire survey was carried out on 40 respondents to prioritise the identified criteria and sub-criteria, and 32 respondents were further surveyed to evaluate a selected number of hotels. Data for all three stages were accumulated from internal and external stakeholders of Bangladesh's hotel industry ranging from policy makers, quality management experts, experienced hotel guests, and top and middle-level hotel executives. Thematic analysis was used during the qualitative stage and eight criteria were uncovered namely: Top Management Commitment and Leadership, Strategic Planning, Service Process Management, Employee Focus, Customer/Guest Focus, Quality Management, Communication, and Business Results together with their corresponding sub-criteria. Subsequently, the relative measurement of Analytic Hierarchy Process (AHP) was applied to prioritise these identified criteria and sub-criteria. Quality Management emerged as the most crucial criterion, and Health and Safety-Security Measures was the most important sub-criterion in addressing this criterion. Additionally, using the absolute measurement of AHP, Hotel Radisson Blu of Chittagong was identified as the best performing hotel among the selected hotels. The performance excellence measurement framework developed for hotel industry is a unique one which can be used by practitioners to evaluate performance of hotels. Though the framework has been developed in the context of Bangladesh, however, the framework can be applied to measure performance of hotels in other countries as well with minor modifications.